APOC3 rs2070667 Associates with Serum Triglyceride Profile and Hepatic Inflammation in Nonalcoholic Fatty Liver Disease. (27th November 2020) - Xu, Qing-Yang; Li, Han; Cao, Hai-Xia; Pan, Qin; Fan, Jian-Gao
Abstract : Single-nucleotide polymorphisms (SNPs) of apolipoprotein C3 ( APOC3 ) play important role in lipid metabolism, and dyslipidemia underlies nonalcoholic fatty liver disease (NAFLD). But the correlation of serum lipidomics, APOC3 SNPs, and NAFLD remains limited understood. Enrolling thirty-four biopsy-proven NAFLD patients from Tianjin, Shanghai, Fujian, we investigated their APOC3 genotype and serum lipid profile by DNA sequencing and ultraperformance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS), respectively. Scoring of hepatocyte steatosis, ballooning, lobular inflammation, and liver fibrosis was then performed to reveal the role of lipidomics-affecting APOC3 SNPs in NAFLD-specific pathological alterations. Here, we reported that APOC3 SNPs (rs4225, rs4520, rs5128, rs2070666, and rs2070667) intimately correlated to serum lipidomics in NAFLD patients. A allele instead of G allele at rs2070667, which dominated the SNPs underlying lipidomic alteration, exhibited downregulatory effect on triacylglycerols (TGs: TG 54 : 7, TG 54 : 8, and TG 56 : 9) containing polyunsaturated fatty acid (PUFA). Moreover, subjects with low-level PUFA-containing TGs were predisposed to high-grade lobular inflammation (TG 54 : 7, rho = − 0.454 and P = 0.007 ; TG 54 : 8, rho = − 0.411 and P  =0.016; TG 56 : 9, rho = − 0.481 and P = 0.004 ). The significant correlation of APOC3 rs2070667 and inflammation grading [G/G vs. G/A+A/A: 0.00 (0.00 and 1.00) vs. 1.50 (0.75 and 2.00), P = 0.022 ] further confirmed its pathological action on the basis of lipidomics-impacting activity. These findings suggest an inhibitory effect of A allele at APOC3 rs2070667 on serum levels of PUFA-containing TGs, which are associated with high-grade lobular inflammation in NAFLD patients.